Mass Hysteria and Dangers of Conformity in Arthur Miller’s The Crucible - LAMOUDI, Nesrine; SOLTANI, Ouahiba (University of Eloued جامعة الوادي, 2024)
Salem witch trials are an important period in New England history that American historians have explored in great detail. Scholars have investigated social, economic, and psychological aspects to identify the underlying causes of the incidents. The trials are regarded as the two most important witch hunts in American history, leading to almost twenty executions. "The Crucible'' is a 1953 play by Arthur Miller, examined 1950s events and emphasized the panic surrounding the Salem witch trials, a present study attempts to shed light on the analysis of the two major themes in ''The Crucible'' play which are the mass hysteria and dangers of conformity and explores the relevance of modern society by examining the events and the issues related to social pressure also the study help to understanding the historical context by provides insight into the historical events surrounding the Salem society helping us understand how fear and conformity can lead to injustices present research adopts the analytical method in order to analyze how miller, through his play, expressed the idea of hysteria and conformity within the historical context, This study reveals that ''The Crucible'' Arthur Miller's play serves as a cautionary tale about the dangers of mass hysteria and manipulation through fear for political purposes. It deals with issues such as how we define justice, what happens when people follow blindly and consequences thereof; therefore The Crucible remains timeless because it reminds us that literature and society are influenced by historical events even decades later. تُعد محاكمات الساحرات في سالم فترة مهمة في تاريخ نيو إنجلاند والتي استكشفها المؤرخون الأمريكيون بقدر كبير من التفصيل. قام الباحثون بالتحقيق في الجوانب الاجتماعية والاقتصادية والنفسية لتحديد الأسباب الكامنة وراء هذه الحوادث. تعتبر المحاكمات أهم مطاردة للساحرات في التاريخ الأمريكي، مما أدى إلى ما يقرب من عشرين عملية إعدام. "البوتقة" مسرحية لآرثر ميلر، تناولت أحداث الخمسينيات وسلطت الضوء على الذعر الذي أحاط بمحاكمات الساحرات في سالم، وتحاول الدراسة الحالية تسليط الضوء على تحليل الموضوعين الرئيسيين في مسرحية البوتقة وهما الهستيريا الجماعية ومخاطر المطابقة واستكشاف أهمية المجتمع الحديث من خلال دراسة الأحداث والقضايا المتعلقة بالضغط الاجتماعي كما تساعد الدراسة على فهم السياق التاريخي من خلال توفير نظرة ثاقبة للأحداث التاريخية المحيطة بمجتمع سالم مما يساعدنا على فهم كيف يمكن أن يؤدي الخوف والمطابقة للمظالم. يتبنى البحث الحالي المنهج التحليلي لتحليل كيفية تعبير ميلر من خلال مسرحيته عن فكرة الهستيريا والامتثال ضمن السياق التاريخي، وتكشف هذه الدراسة أن مسرحية آرثر ميلر "البوتقة" بمثابة حكاية تحذيرية حول مخاطر الجماهير الهستيريا والتلاعب من خلال الخوف لأغراض سياسية. إنه يتعامل مع قضايا مثل كيفية تعريف العدالة، وما يحدث عندما يتبع الناس بشكل أعمى وعواقب ذلك؛ لذلك تظل البوتقة خالدة لأنها تذكرنا بأن الأدب والمجتمع يتأثران بالأحداث التاريخية حتى بعد مرور عقود.
Literature and Civilization
Keywords: Hysteria; Conformity; Salem Witch Trials; Massachusetts; McCarthyism; Red Scar.; الهستيريا، المطابقة، محاكمات ساحرة سالم، ماساتشوستس، المكارثية، الندبة الحمراء